2007
DOI: 10.1038/sj.gt.3303025
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of neuropathic pain in an animal model of spare nerve injury following oral immunization with recombinant adenovirus serotype 5-mediated NR2B gene transfer

Abstract: Spinal N-methyl-D-aspartate receptor 2B subunit (NR2B)-increased expression plays an important role in the facilitation and maintenance of the persistent pain state due to peripheral nerve injury. A vaccination strategy to reduce the expression of brain protein is feasible and may have therapeutic potential for neurological disorders. Thus, we investigated the effect of oral immunization with recombinant adenovirus serotype 5-mediated NR2B gene transfer (rAd5/NR2B) for the modulation of neuropathic pain. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Spinal administration of NMDAR antagonists attenuates tissue or nerve injury‐induced pain hypersensitivity, suggesting the critical role of NMDARs in central sensitization (Tan et al,2005, 2010; Wang et al,2007; Qu et al,2009; Wu and Zhuo,2009). A large body of evidence has indicated that direct injection of NMDA onto the spinal dorsal horn of intact animals is also able to elicit mechanical allodynia and thermal hyperalgesia (Sato et al,2003; Shimoyama et al,2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal administration of NMDAR antagonists attenuates tissue or nerve injury‐induced pain hypersensitivity, suggesting the critical role of NMDARs in central sensitization (Tan et al,2005, 2010; Wang et al,2007; Qu et al,2009; Wu and Zhuo,2009). A large body of evidence has indicated that direct injection of NMDA onto the spinal dorsal horn of intact animals is also able to elicit mechanical allodynia and thermal hyperalgesia (Sato et al,2003; Shimoyama et al,2005).…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, non‐NMDA subtype glutamate receptors, including AMPA and kainate receptors (Li et al,1999; Yoshimura and Jessell,1990), have been indicated to mediate the majority of fast excitatory glutamatergic synaptic transmission onto the dorsal horn neurons, whereas the contribution of NMDARs to physiological pain is dispensable because of their voltage‐dependent Mg 2+ blocking property at resting membrane potential (Yoshimura and Jessell,1990). After peripheral tissue or nerve injury, NMDA receptors, especially NR2BR, undergo a long‐lasting increase in their functions and play a critical role in pathological pain (Tan et al,2005; Wu et al,2005; Iwata et al,2007; Wang et al,2007). However, the molecular mechanisms underlying the prolonged NR2BR hyperactivity are not fully understood as yet.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated that many factors can contribute to the development of neuropathic pain, such as inflammation [57], and changes in neurotransmission [58,59]. Neuropathic pain appears in many anomalous situations, including spinal cord injury [60], diabetes, peripheral nerve injury [61,62] and in some inflammatory conditions [24,41,63,64]. A growing body of evidence has shown that activation of the PI3K/Akt pathway in the spinal cord contributes to hyperalgesia in many neuropathic models [46].…”
Section: Pi3k/akt Pathway and Neuropathic Painmentioning
confidence: 99%
“…NR1 is essential for NMDAR activity and interaction with NR2A and NR2B subunits confers functional variability. In particular, blocking the activity of NR2B subunit with antagonists [29], vaccination strategies [33] or small interfering RNAs [28] prevents the development of neuropathic pain. Recently, morphine exposure [19] and diabetes [31] have been shown to induce an up-regulation of NMDAR subunits within the spinal dorsal horn, contributing No changes in PKC␥ mRNA levels of expression were detected in the dorsal spinal cord 1 or 14 days after spinal hemisection but a significant increase in PKC␥ transcripts was observed 28 days after the lesion (*p < 0.05 vs. CTL and other time-points).…”
mentioning
confidence: 99%